2021
DOI: 10.21037/apm-20-295
|View full text |Cite
|
Sign up to set email alerts
|

Randomized research on the mechanism of local oxygen therapy promoting wound healing of diabetic foot based on RNA-seq technology

Abstract: Background: High purity oxygen therapy has good clinical efficacy in the treatment of diabetic foot (DF), but its mechanism of promoting wound healing has been unclear.Methods: Patients with DF were randomly divided into an experimental group and a control group. The experimental group was given local oxygen therapy (LOT) by a micro-oxygen therapy instrument, which administered uninterrupted >95% pure oxygen for 24 h at a flow rate of 3 mL/h. Six skin samples from the experimental group before and after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Diabetic foot ulcers (DFU) affect approximately 25% of diabetes patients (Li et al, 2021). When patients develop foot ulcers, they frequently face the risk of subsequent infection, amputation or even death (Wang, Pan, Gao, Qin, & Wang, 2021). An estimated 85% of them will require amputations (Boulton, 2019), and more than half of them will die within 5 years (Armstrong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic foot ulcers (DFU) affect approximately 25% of diabetes patients (Li et al, 2021). When patients develop foot ulcers, they frequently face the risk of subsequent infection, amputation or even death (Wang, Pan, Gao, Qin, & Wang, 2021). An estimated 85% of them will require amputations (Boulton, 2019), and more than half of them will die within 5 years (Armstrong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to paying attention to the treatment of systemic factors, such as the control of blood sugar, blood pressure, blood lipid, anti-infection and the improvement of microcirculation, we must also pay attention to the standardized treatment of chronic wound itself. Only the comprehensive coordinated treatment of whole body and local can promote the healing of chronic difficult wound ( 22 , 23 ). DFU healing is a multi-step process that requires the coordination of 4 distinct but overlapping physiologically logical phases, including hemostasis, inflammation, proliferation, and remodeling ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other, a participant and outcome blind RCT 109 , which was assessed at low risk of bias, showed greater percentage wound closure in the topical oxygen group compared to sham therapy at 12 weeks. The remaining seven studies [113][114][115][116][117][118][119] were at high risk of bias as: neither participants nor outcome assessors were blind to the intervention allocation, [113][114][115][116][117][118][119] groups differed in baseline areas, studies reported no between group analysis, 115,117,118 or reported an absolute rather than relative area reduction 116 and thus any positive results reported were of low certainty.…”
Section: Outcome: Reduction In Ulcer Areamentioning
confidence: 99%